The impact of physical activity variety on physical activity participation - Tyler M. Dregney; Chelsey Thul; Jennifer A. Linde; Beth A. Lewis (PLoS ONE, 2025)
Background and aims Variety (i.e., multiple types of activities) may be effective for increasing physical activity (PA) based on previous research; however, research is needed to evaluate variety’s impact on psychosocial variables. Methods This exploratory study examined the effect of a home-based PA variety intervention on PA participation and psychosocial variables (motivation, psychological needs satisfaction, enjoyment, boredom, variety perception, PA feeling, self-efficacy, and affect) in an eight-week randomized intervention trial. Participants (n = 47; mean age, 19.9 + /- 1.9; 75% female) were low-active, 18–25-year-old college students randomized to participate in the PA variety intervention or the consistency comparison condition. All participants received weekly individual counseling. The PA variety intervention received 14 unique high intensity interval training (HIIT) workouts with instructions to complete at least three different workouts per week, and the consistency comparison received one HIIT workout to complete at least three times per week. Priori comparisons and between groups analysis of covariance were used to examine findings. Results Participants in the variety condition reported marginally significant more weekly moderate-to-vigorous PA (p = .072) over the course of the intervention and higher psychological needs satisfaction (p = .099) at four weeks relative to the comparison. The variety intervention condition reported significantly higher perceived autonomy (p = .013) within psychological needs at four weeks, PA feelings of tranquility (p = .005) at eight weeks, and PA self-efficacy (p = .025) at eight weeks relative to the comparison. Conclusions This exploratory study revealed there was preliminary evidence that variety may lead to improved psychological responses to PA among college-age individuals, although findings should be interpreted with caution given the use of marginal significance. Future studies should examine how a variety of different activities (e.g., cycling, tennis, group fitness classes) influence motivation and PA, in addition to including larger and more diverse samples. Practitioners should support clients’ psychological needs and provide home-based PA options.